#TITLE_ALTERNATIVE# - JULIUS HUTAGALUNG , MERLIN
Relay is one of the important protective device in the protection of power system. Relay give order to circuit breaker to open if fault happens. In the high voltage transmission system, directional overcurrent relay and distance relay are often used as the main component of protection system. It's easy to calculate the coordination of overcurrent relay and distance relay manually. But in the more complex system, consists of many source and load, it can be difficult. Because of that an optimazion method is needed to solve the problem quickly, efficiently and simultaneously. This final project study about optimazion of directional overcurrent relay and distance relay's coordination in complex system. The coordination equation is outlined in linier equation, with TMS (Time Multiple Setting) and Tz2 (Distance relay second zone) as an optimized value. The objective is to get minimum operating time without violating Coordination Interval (CI). The optimazion method has been simulated in radial system, 8-bus 7 lines IEEE. The simulation result shown that this optimazion method had succeed to solve the relay coordination problems efficiently, quickly and simultaneously.